Assessment of Scapula Muscle Strength in Housemaids (Medico Legal Update, 2021)
Introduction: Neck and upper limb musculoskeletal disorders are a major source of disability which is alsoresulting in economic loss. Housemaids are exposed to repetitive tasks which causes them to be at high riskof neck pain. This result in increased burden on health care costs and also adds to reduced work productivity.The aim of the study is to evaluate scapula muscle strength in housemaids to determine magnitude of theproblem.Methodology: A total of 100, divided as 50 participants in housemaid group with neck pain and 50 agematched normal individuals in the asymptomatic group were recruited for the study. Self made questionnaireand scapula muscle strength were tested using push - pull dynamometer.Results and Discussion: The study highlights the weakness of scapula muscle strength with neck pain inhousemaids as compared to asymptomatic group. This gives us an insight into significance of scapula musclestrength in neck pain cases which will help us in formulating effective treatment strategies for treating neckpain cases.